Cholesterol synthesis inhibitors protect against platelet-activating factor-induced neuronal damage - Williams Alun; Rumbold Louis; Bate Clive (Journal of Neuroinflammation, 2007)
Abstract Background Platelet-activating factor (PAF) is implicated in the neuronal damage that accompanies ischemia, prion disease and Alzheimer's disease (AD). Since some epidemiological studies demonstrate that statins, drugs that reduce cholesterol synthesis, have a beneficial effect on mild AD, we examined the effects of two cholesterol synthesis inhibitors on neuronal responses to PAF. Methods Primary cortical neurons were treated with cholesterol synthesis inhibitors (simvastatin or squalestatin) prior to incubation with different neurotoxins. The effects of these drugs on neuronal cholesterol levels and neuronal survival were measured. Immunoblots were used to determine the effects of simvastatin or squalestatin on the distribution of the PAF receptor and an enzyme linked immunoassay was used to quantify the amounts of PAF receptor. Results PAF killed primary neurons in a dose-dependent manner. Pre-treatment with simvastatin or squalestatin reduced neuronal cholesterol and increased the survival of PAF-treated neurons. Neuronal survival was increased 50% by 100 nM simvastatin, or 20 nM squalestatin. The addition of mevalonate restored cholesterol levels, and reversed the protective effect of simvastatin. Simvastatin or squalestatin did not affect the amounts of the PAF receptor but did cause it to disperse from within lipid rafts. Conclusion Treatment of neurons with cholesterol synthesis inhibitors including simvastatin and squalestatin protected neurons against PAF. Treatment caused a percentage of the PAF receptors to disperse from cholesterol-sensitive domains. These results raise the possibility that the effects of statins on neurodegenerative disease are, at least in part, due to desensitisation of neurons to PAF.